КОМПЕНСАЦИЯ РЕАКТИВНОЙ МОЩНОСТИ В КОМПЛЕКТЕ «РАЗРЯДНАЯ ЛАМПА – ПРА» - Говоров , Ф.П.; Говоров , В.Ф.; Ганус, А.И. (Інститут електродинаміки НАН України, Київ, 2012)
Scientific-methodical and technical basis for reactive power compensation included "discharge lamp apparatus admits-regulated" taking into account the nonlinearity of its characteristics. References 3.